Critical Current Measurements of HTS Tapes Using Pulsed Current in High Fields at Low Temperatures - Tsuchiya, Y.; Sakai, I.; Mizuno, K.; Kohama, Y.; Yoshida, Y.; Awaji, S. (IEEE transactions on applied superconductivity, 2023)
High-temperature superconducting (HTS) tapes have been the subject of intensive research for various applications. In addition to their use at high temperatures in liquid nitrogen cooling, they are expected to be utilized in ultra-high field magnets at 30 T or higher at low temperatures, as well as in compact fusion reactors and rotating machines in intermediate temperature ranges. Each company has made significant strides in improving the critical current of HTS tapes, necessitating the development of test facilities with variable temperatures and high currents, such as those of the 2000 A and 20 T class. Typically, a steady current is employed for critical current measurements. In this study, we focus on pulsed current measurements to perform critical current measurements at high currents in limited spaces with high magnetic fields. A probe with a low inductance was fabricated, and a trapezoidal pulse current of 2-10 ms was applied to the sample using a 500 A-class pulse power supply. The current and voltage of the sample were recorded using a high-resolution isolated oscilloscope. By integrating this system with a 20 T cryogen-free superconducting magnet and a He-flow cryostat, critical currents in commercially available HTS tapes with 4 mm width were measured at temperatures ranging from 4 K to 77 K and magnetic fields up to 19 T. The Lorentz force caused the probe to oscillate and the voltage leads to swing, resulting in substantial voltage noise. Noise reduction down to 0.6 μV was achieved under 19 T, 500 A conditions, by fixing the voltage leads and changing the direction of Lorentz forces on the probe. The field dependences of the critical currents in a HTS REBCO tape characterized with pulsed and steady-state currents were compared and determined to be equivalent.